The right of freedom of press under the Printing Presses and Publication Act 1984 / Ahmad al-Hady Abdul Razak … [et al.] - Abdul Razak, Ahmad al-Hady; Shuhaimi, Elia Atiqah; Ahmad Shah, Farhana; Ahmadi, Raden Farah Shirazee; Shafiuddin, Suhaila (2010)
Media plays a crucial role in shaping and altering public opinion through various means of reporting. Freedom of press is not a right exclusive for the media community only. Malaysian citizen also should be attentive to fight for freedom of press as it should be their right to freedom of expression. Freedom of expression includes one right to receive information. In other country such as India, freedom of press is included under freedom of speech and expression. In Malaysia, the situation is different where by press freedom is not clearly protected as one of the fundamental liberties in Federal Constitution. The extent of freedom of press in Malaysia can be seen in one of the legislation in the country, i.e. Printing Presses and Publications Act 1984(the Act). The Act has attracted much criticisms and disapproval especially among media community and Malaysian journalists. Their rights to express opinion and information are always oppressed by the extensive scope imposed under the Act. The absolute discretionary power of the Home Minister is seen as a hindrance to the pave of press freedom. With exclusion of judicial review and principles of natural justice under the Act, it strengthens the power of the Home Minister and consequently weakened press freedom. This project paper composed of in-depth study of the position of freedom of press under Article 10 (1) (a) of the Federal Constitution and the extent of freedom of press under the Act.